Who thinks what about e‐cigarette regulation? A content analysis of UK newspapers - Patterson, Chris (Addiction, 2016)
AIMS: To establish how frequently different types of stakeholders were cited in the UK media debate about e‐cigarette regulation, their stances towards different forms of e‐cigarette regulation, and what rationales they employed in justifying those stances. METHODS: Quantitative and qualitative content analyses of 104 articles about e‐cigarette regulation published in eight UK and three Scottish national newspapers between 1 January 2013 and 31 December 2014. RESULTS: Reporting on e‐cigarette regulation grew significantly (P < 0.001) throughout the sample period. Governments and regulatory bodies were the most frequently cited stakeholders and uniformly supported regulation, while other stakeholders did not always support regulation. Arguments for e‐cigarette regulation greatly outnumbered arguments against regulation. Regulating purchasing age, restricting marketing and regulating e‐cigarettes as medicine were broadly supported, while stakeholders disagreed about prohibiting e‐cigarette use in enclosed public spaces. In rationalizing their stances, supporters of regulation cited child protection and concerns about the safety of e‐cigarette products, while opponents highlighted the potential of e‐cigarettes in tobacco cessation and questioned the evidence base associating e‐cigarette use with health harms. CONCLUSIONS: In the UK between 2013 and 2014, governments and tobacco control advocates frequently commented on e‐cigarettes in UK‐wide and Scottish national newspapers. Almost all commentators supported e‐cigarette regulation, but there was disagreement about whether e‐cigarette use should be allowed in enclosed public spaces. This appeared to be linked to whether commentators emphasized the harms of vapour and concerns about renormalizing smoking or emphasized the role of e‐cigarettes as a smoking cessation aid.